Formulation and characterization of polypropylene structural foam for large parts - Esteves, F. R. (2011)
Structural foams (SF) are a material solution for injection moulding, in short productions series, of large size parts. They are a composite material constituted by two skins without cells and a cellular core. Injection of SF is a low pressure process, ideal for producing large parts. For this reason they are a viable alternative for light moulding tools. The right formulation of structural foam and the use of adequate processing conditions are important to optimize the performance of the plastics part. In this paper are presented several formulations of polypropylene and blowing agent for injection moulding using hybrid moulds. The rheological, morphological and mechanical characterization is made to evaluate structural foam performance.